2016
DOI: 10.1371/journal.pone.0169065
|View full text |Cite
|
Sign up to set email alerts
|

A Model Based Cost-Effectiveness Analysis of Routine Genotyping for CYP2D6 among Older, Depressed Inpatients Starting Nortriptyline Pharmacotherapy

Abstract: ObjectiveGenotyping for CYP2D6 has the potential to predict differences in metabolism of nortriptyline. This information could optimize pharmacotherapy. We determined the costs and effects of routine genotyping for old aged Dutch depressed inpatients.MethodsWith a decision-tree, we modelled the first 12 weeks of nortriptyline therapy. Direct costs of genotyping, hospitalization, therapeutic drug monitoring and drugs were included. Based on genotype, patients could be correctly, sub-, or supratherapeutically do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…The QHES checklist can generate a score between 0 and 100, while a score of 75 and more is of the highest quality [40] (Supplemental Table 1). Three reviewers assessed the quality of all included studies [41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58] independently, when results differed (N = 3) though, the consensus was reached through discussion by all authors.…”
Section: Quality Of Reporting Assessmentmentioning
confidence: 99%
“…The QHES checklist can generate a score between 0 and 100, while a score of 75 and more is of the highest quality [40] (Supplemental Table 1). Three reviewers assessed the quality of all included studies [41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58] independently, when results differed (N = 3) though, the consensus was reached through discussion by all authors.…”
Section: Quality Of Reporting Assessmentmentioning
confidence: 99%
“…Majority of the studies were conducted in European and American countries (43 studies) (73%), while studies related to HLA-B*58:01allopurinol and HLA-B*15:02-carbamazepine were mostly found in Asian countries. Most studies investigated the therapeutic area of cardiovascular diseases (24 studies) , followed by gout (8 studies) [40][41][42][43][44][45][46][47], human immunodeficiency virus (HIV) infection (8 studies) [48][49][50][51][52][53][54][55], autoimmune diseases (8 studies) [56][57][58][59][60][61][62][63], and epilepsy/neuropathic pain (6 studies) [64][65][66][67][68][69], cancer (3 studies) [70][71][72], major depressive disorder [73], and hormone replacement therapy [74].…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…CYP2D6 and nortriptyline-induced anticholinergic symptoms The CUA with model-based economic evaluation in the Netherland study showed that CYP2D6 screening for adjusting dose before starting nortriptyline compared to no screening would not be cost-effective since CYP2D6 was not potentially related to the reduction of ADRs and to the increased efficacy of nortriptyline in a major depressive disorder [73].…”
Section: Major Depressive Disordermentioning
confidence: 99%
“…A recent review of the literature concluded that treatment decision making including the use of pharmacogenetic tests appears to be cost-effective or cost-saving for a high percentage of the drugs for which the FDA provided recommendations (Verbelen et al ., 2017). Most of the economic analysis concerning the use of pharmacogenetic tests in patients receiving antidepressants was done through the construction of pharmacoeconomic models that involved the simulation of patient cohorts for which costs and outcomes were estimated based on literature data and existing guidelines (Berm et al ., 2016). Furthermore, among the few available studies that included data collected on real patient cohorts, most were not conducted by independent researchers but by the companies that launched pharmacogenetic tools on the market (Bousman and Hopwood, 2016).…”
Section: Introductionmentioning
confidence: 99%